Effect of Health Education on Adolescents' Knowledge and Attitudes About Promiscuous Sex - Fitriani Fitriani; Nurekawati; Dewi Sartika MS; Nelly Nugrawati; Siti Alfah (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2022)
Introduction: Indonesian teenagers seem more tolerant of a premarital sexual lifestyle or free sex. Many factors influence this behaviour, one of which is attitudes and knowledge about free sex itself. This knowledge and perspective can be improved by providing health education or counselling. Objective: find out the effect of health education on the inside and attitudes of adolescents about free sex in SMK Negeri 6 Makassar.Methods: One Group pre-test post-test design is the pre-experimental research type with the research design. The sample of this research includes 84 students at SMK Negeri 6 Makassar using Cluster Sampling as a sampling technique. Research instrument using a questionnaire—analysis of the data used in bivariate analysis, Paired Sample T-test. Results: shows an increase in the number of respondents who have good knowledge between before and after health education, namely a mean change of 7,131 (± 3,229) of98.8% with a p-value of 0.000. And there is an increase in the number of respondents who have a good attitude between before and after health education, namely: a mean change of 3,917 (± 3,860), as much as 100% with a p-value of 0.000. Conclusion: from this study, there is an effect of health education on students' knowledge and attitudes (i) about free sex at SMK Negeri 6 Makassar